Ocorrência de parasitoides associados a pragas do milho (Zea mays L.) cultivado em diferentes sistemas de produção - Silva, Rafael Braga da (2013)
The aim of this study was to determine the occurrence of parasitoids of the major pests of maize (Zea mays L.) cultivated in different production systems. The experiment was conducted at the Embrapa Milho e Sorgo, in Sete Lagoas, State of Minas Gerais, Brazil, in conventional production systems, organic, organic intercropped with beans (Phaseolus vulgaris L.) and organic exclusive. In the collections of plants made in conventional maize and organic maize were only obtained larvae of Spodoptera frugiperda, with the emergence of the parasitoids Archytas sp.1, Archytas sp.2, Cotesia sp., Dolichozele koebelei, Eiphosoma laphygmae, Eiphosoma sp.1, Eiphosoma sp.2, Euplectrus sp., Exasticolus sp. nov., Hyphantrophaga sp. and Winthemia sp. Cremastinae species and Ophion flavidus occurred in organic maize; Campoletis sp. in conventional maize. In the ear of conventional maize and ear of organic maize were obtained larvae of Diatraea saccharalis, Dichomeris famulata, Euxesta spp., Helicoverpa zea, Megaselia seticauda and S. frugiperda. Megaselia seticauda was first reported in the ears of maize in Brazil. The parasitoids obtained from the ears of conventional maize and organic maize in S. frugiperda were: Hyphantrophaga sp. occurring in both areas, Glyptapanteles sp. only in the conventional maize and Microcharops sp. only in the organic maize, for H. zea in the organic maize parasitized larvae were not obtained, in the conventional maize, occurred the parasitoids Aleiodes sp. and Copidosoma sp. Apanteles sp. and Phanerotoma sp. occurred on D. famulata in the conventional maize and organic maize; Chelonus (Microchelonus) sp. nov., Microcharops sp. and Perilampus sp. occurred only in the conventional maize. Apsilophrys sp. occurred only in organic maize. These are the first records of Apanteles sp., Chelonus (Microchelonus) sp. nov., Microcharops sp., Perilampus sp. and Phanerotoma sp. on D. famulata. In Euxesta spp. in the organic maize were not obtained larvaes killed by parasitoids in the conventional maize on Euxesta spp. occurred the parasitoid Dettmeria sp. About D. saccharalis and M. seticauda, there were not obtained parasitoids. In the collections of stalks of conventional maize and organic maize, there was a prevalence of D. saccharalis, S. frugiperda occurred only in conventional maize. There were not observed larvaes of S. frugiperda killed by parasitoids, but for D. saccharalis, occurred, in two areas, the parasitoid Lixophaga sp. In the collections of plants, in the organic maize exclusive and organic maize intercropped with beans, the parasitoids obtained from the larvae of S. frugiperda were Archytas sp., Campoletis sp., Cotesia sp., D. koebelei, E. laphygmae, Eiphosoma sp.1, Eiphosoma sp.2, Eiphosoma sp.3, Eiphosoma sp.4, Eiphosoma sp.5, Glyptapanteles sp., Microcharops sp. and O. flavidus. The parasitoids Aprostocetus sp., Chelonus insularis, Colpotrochia sp. nov. and Ichneumoninae were observed only in the exclusive organic maize, while Apanteles sp. and Eiphosoma sp.6 only in the organic maize intercropped with beans. From the pests of the ear of maize collected in the organic maize exclusive and in the organic maize intercropped with beans occurred larvaes of D. famulata, Euxesta spp., H. zea, M. seticauda and S. frugiperda. From these only larvaes of H. zea and D. famulata were parasitized. The index of parasitism of H. zea by Archytas sp. was similar in both areas, the parasitoid of D. famulata, Apsilophrys sp. was observed in all samples of organic maize intercropped with beans, but it did not occur in any collection of the exclusive organic maize. In these samples were not obtained for parasitoids Euxesta spp., M. seticauda and S. frugiperda. In the collections of stalks in organic maize exclusive and organic maize intercropped with beans were obtained only larvaes of D. saccharalis without the occurrence of parasitoids. In both experiments the number of larvaes of the pests collected was low, new associations and new species of parasitoids reported represent the possibility of the exploitation of these natural enemies in the control of pests in the culture of maize.